Implementation of Integrity Values in The Tarbiyatul Muallimin Al-Islamiyah Curriculum in Character Building and Well-Being of Santri - Rosidah, Istifaur; Agustin, Maulid (Medina-te : Jurnal Studi Islam, 2025)
This study aims to analyze the implementation of integrity values ​​in the Tarbiyatul Muallimin Al-Islamiyah (TMI) Curriculum and evaluate its impact on the well-being of students at the Darul Istiqomah Islamic Boarding School in Bondowoso. This study uses a qualitative approach with a case study method. Data were collected using observation techniques, in-depth interviews, and documentation studies. Data analysis techniques were carried out interactively with the Miles and Huberman model, which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that integrity values ​​such as honesty, responsibility, and discipline are systematically integrated into the learning process and daily lives of students through an exemplary approach, habituation, and character building. The supporting factors for the implementation of integrity include the commitment of the Islamic boarding school leadership, the competence of educators, and parental involvement. On the other hand, the challenges faced include the heterogeneity of the students' backgrounds, the gap in parents' perceptions, and communication barriers. Overall, the implementation of integrity values ​​makes a positive contribution to improving the well-being of students in psychological, social, and academic aspects. The results of this study emphasize the importance of integrating character education into the Islamic boarding school education system as a foundation for forming a generation that excels morally and spiritually.